Sistem Pendukung Keputusan Pemilihan Pengajar Les untuk Siswa Lembaga Bimbingan Belajar Dengan Metode Simple Additive Weight - Felix, Kendrick; Mettalia, Maitriyana; Sabatini, Tiffany; Itan, Vincent (Journal of Digital Ecosystem for Natural Sustainability, 2024)
The goal of education is to help students develop their potential for personal, societal, and national benefits through an organized learning process between teachers and students. Through one-on-one or group tutoring sessions, tutoring centers are essential in helping students overcome scholastic obstacles and advance their abilities. Nevertheless, a lot of tutoring facilities, including "Let's Shine," continue to use manual scheduling techniques, sometimes with Excel, which results in inefficiencies and frequent changes. In order to improve tutor scheduling, this study suggests using the Simple Additive Weighting (SAW) method, which gives priority to factors such tutor status, subject type, time, day, number of students, and difficulty level. Management interviews and observation were used in the data collection process. The SAW method streamlines scheduling with an objective, data-driven approach that should increase productivity and decrease revisions.